Processing Compostable Pla/Organoclay Bionanocomposite Foams by Supercritical co2 Foaming for Sustainable Food Packaging - Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Riveros-Faba, S (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This article proposes a foaming method using supercritical carbon dioxide (scCO2) to obtain compostable bionanocomposite foams based on PLA and organoclay (C30B) where this bionanocomposite was fabricated by a previous hot melt extrusion step. Neat PLA films and PLA/C30B films (1, 2, and 3 wt.%) were obtained by using a melt extrusion process followed by a film forming process obtaining films with thicknesses between 500 and 600 μm. Films were further processed into foams in a high-pressure cell with scCO2 under constant conditions of pressure (25 MPa) and temperature (130 °C) for 30 min. Bionanocomposite PLA foams evidenced a closed cell and uniform cell structure; however, neat PLA presented a poor cell structure and thick cell walls. The thermal stability was significantly enhanced in the bionanocomposite foam samples by the good dispersion of nanoclays due to scCO2, as demonstrated by X-ray diffraction analysis. The bionanocomposite foams showed improved overall mechanical performance due to well-dispersed nanoclays promoting increased interfacial adhesion with the polymeric matrix. The water uptake behavior of bionanocomposite foams showed that they practically did not absorb water during the first week of immersion in water. Finally, PLA foams were disintegrated under standard composting conditions at higher rates than PLA films, showing their sustainable character. Thus, PLA bionanocomposite foams obtained by batch supercritical foaming seem to be a sustainable option to replace non-biodegradable expanded polystyrene, and they represent a promising alternative to be considered in applications such as food packaging and other products. © 2022 by the authors.